Timing and tactical analysis of player substitutions in the UEFA Champions League - Rey, E.; Lago-Ballesteros, J.; Padron-Cabo, A. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to examine the influence of situational variables on timing and tactics of substitutions in elite soccer. The sample was constituted by 677 substitutions made over the 124 matches played in the 2013-14 UEFA Champions League. To determine factors that affect substitution times, one-way ANOVA and Student's t-test were used. In a second instance, a chi-square analysis was carried out to establish if there was an association between each situational variable and the tactics of substitution. Data mining technique (J48 decision tree) was used to find optimal splits in substitution times, which lead to enhanced probability of success. Coaches tend to hold onto substitutions later when the team is ahead, but make substitutions earlier when either tied or behind